2014
DOI: 10.1245/s10434-014-3535-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Neoadjuvant Endocrine Therapy with Aromatase Inhibitors in Elderly Women with Hormone Receptor-Positive Breast Cancer

Abstract: Background Aromatase inhibitors (AIs) are more effective than tamoxifen as neoadjuvant endocrine therapy (NET) for hormone receptor (HR)-positive breast cancer. Here we report the surgical and long-term outcome of elderly postmenopausal patients with locally advanced, HR-positive breast cancer treated with preoperative AIs.MethodsBetween January 2003 and December 2012, 144 postmenopausal patients inoperable with breast conservative surgery (BCS) received letrozole, anastrozole, or exemestane as NET. Patients u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…A retrospective observational study by Grassadonia showed that clinical response was strongly correlated with BCS and that BCS was an independent prognostic factor for DFS and OS. 12 Our study showed a correlation between clinical response and the type of surgery; the type of surgery was associated with patient prognosis. These results also align with findings of previous reports.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A retrospective observational study by Grassadonia showed that clinical response was strongly correlated with BCS and that BCS was an independent prognostic factor for DFS and OS. 12 Our study showed a correlation between clinical response and the type of surgery; the type of surgery was associated with patient prognosis. These results also align with findings of previous reports.…”
Section: Discussionmentioning
confidence: 56%
“…Clinical response to NET is associated with surgical outcome, including conversion from mastectomy to breast-conserving surgery (BCS). 12 However, there are few reports examining the association of clinical response to NET with long-term outcomes. In this report, we examined long-term outcomes of patients who received neoadjuvant exemestane treatment for 24 weeks in a multicentre prospective clinical trial and found that clinical response to NET is an independent predictive marker for long-term survival in postmenopausal patients with endocrine-responsive breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of ORR, the largest trial (Z1031 trial) did not demonstrate a significant difference between exemestane (62.9%), letrozole (74.8%), and anastrozole (69.1%) (Table 2 ) [ 53 , 54 ]. Other studies comparing aromatase inhibitors also did not demonstrate superiority of any one agent (Table 2 ) [ 28 , 65 , 66 ]. In terms of the BCS rate, there was no significant difference found between the types of aromatase inhibitors or fulvestrant (Table 2 ) [ 28 , 53 , 54 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 97%
“…Neo-adjuvant chemotherapy reduces tumour size and increases the numbers of patients suitable for surgery, however no difference is seen by age for complete pathological response [ 133 ]. Neo-adjuvant endocrine therapy is of benefit in post-menopausal patients with early breast cancer, improving WLE rates, disease free survival and overall survival [ 134 , 135 ].…”
Section: Age Associated Treatment By Molecular Subtypementioning
confidence: 99%